1984
DOI: 10.1002/1097-0142(19840315)53:6<1385::aid-cncr2820530628>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of locally advanced extremity soft tissue sarcomas by function-saving resection and brachytherapy

Abstract: Amputation has often been advised for the treatment of deep‐seated or bulky soft tissue sarcomas of the limb because of proneness to local recurrence after conservative resection. The authors evaluated the efficacy of local control by means of function‐preserving resection and high‐dose brachytherapy of the tumor bed using Iridium‐192 implants in 33 patients with locally advanced sarcomas, 17 without prior therapy and 16 with locally recurrent tumors. Local control was achieved in 100% of the previously untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…[49] 1987 Radiotherapy Shiu et al . [50] 1984 Radiotherapy O'Sullivan et al . [51] 2002 Radiotherapy…”
Section: Thighmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] 1987 Radiotherapy Shiu et al . [50] 1984 Radiotherapy O'Sullivan et al . [51] 2002 Radiotherapy…”
Section: Thighmentioning
confidence: 99%
“…The concern with radiation therapy is the complications it causes with wound healing. Reported complications have ranged from 33%-44% in the past, with severe morbidity in 22%-27% of patients [48][49][50] . Abramson et al [5] however only reported a 12.5% wound complication rate, including a patient who developed radiation necrosis and required a second free tissue transfer months after his initial treatment.…”
Section: Neoadjuvant and Adjuvant Therapymentioning
confidence: 99%
“…335 From the 1970s, following the original concepts introduced in the 1960s, 6 adjuvant external-beam radiation, brachytherapy, and chemotherapy in combination with limited surgery were identified as effective modalities in terms of survival for patients with bone and soft tissue sarcomas. 272,288,329,336 In breast carcinomas, combined radiation and chemotherapy had the lowest local recurrence and best overall survival rates compared with either therapy alone. 337 After it was confirmed that operable breast carcinoma treated with radiation and chemotherapy reduced local failure significantly better than either modality alone, the combined modality became standard therapy.…”
Section: Radiation Therapymentioning
confidence: 99%
“…A dose of 45 Gy (4500 rads) by this method is equivalent to 60 Gy (600 rads) by external beam irradiation. While attempts at limbsparing surgery using adjuvant therapies may increase the risk of local recurrence, limbsparing surgery with adjuvant radiation and chemotherapy has proved to be as effective as amputation and chemotherapy in terms of survival [22]. Local recurrence may not necessarily have an adverse effect on overall survival, particularly in low-grade lesions.…”
Section: Managementmentioning
confidence: 99%